2016
DOI: 10.1007/978-3-319-42085-1_51
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Reliability of WSN Through Wireless Energy Transfer

Abstract: Abstract. Communication reliability is the ability of the network to last long enough without breaking communication between neighbouring nodes that relay information to the final destination. The transfer of energy from the base station to largely spatially distributed sensor nodes in a network with concurrent data transmission is studied. Concurrent data and energy transfer methods require separation of their frequencies and optimum distance between nodes and Energy Transmitters (ETs). Three techniques of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Earlier research in wireless power transfer considered transfer over single hops until [22] demonstrated the possibility of transferring energy over multihops. Their method gives room for possibility of neighboring nodes to charge energy deprived nodes that may be outside the charging range of energy charging devices like energy transmitters [22,60]. Initial power transfer approaches had limitations in usage due to requirements such as close contact, continuous line of sight, and accurate alignment in charging direction.…”
Section: Wireless Energy Transfermentioning
confidence: 99%
“…Earlier research in wireless power transfer considered transfer over single hops until [22] demonstrated the possibility of transferring energy over multihops. Their method gives room for possibility of neighboring nodes to charge energy deprived nodes that may be outside the charging range of energy charging devices like energy transmitters [22,60]. Initial power transfer approaches had limitations in usage due to requirements such as close contact, continuous line of sight, and accurate alignment in charging direction.…”
Section: Wireless Energy Transfermentioning
confidence: 99%